Robotic cholecystectomy and cholecystoenteric fistula closure in a female with remote cholangitis - Baratta, Vanessa M (J Surg Case Rep, 2019)
Cholecystocolic fistula (CCF), a connection between the gallbladder and neighboring colon, is a rare entity with little consensus as to the optimal surgical management. Existing case reports have described both open and laparoscopic repairs. We describe the first reported case of a successful robotic repair of a CCF in a 50-year-old woman diagnosed with cholangitis 5 years prior to surgery. The patient had a longitudinal follow-up by a single surgeon, allowing for early diagnosis and repair. This case also includes radiographic imaging over 5 years during the index hospitalization and preoperative workup. This allows for a glimpse into the natural pathogenesis of this disease. After robotic surgery, the patient made a complete recovery with no postoperative complications.